Clinical Outcome and Efficacy of Antegrade Colonic Enemas Administered via an Indwelling Cecostomy Catheter in Adults With Defecatory Disorders. Issue 4 (April 2015) - Patton, Vicki; Lubowski, David Z.
<x xml:space="preserve">Abstract</x> BACKGROUND: Antegrade colonic enemas are used in selected adult patients with defecatory disorders. Conduit stenosis requiring revisional surgery is common. OBJECTIVE: The aim of the study was to determine whether stenosis could be avoided by using an indwelling antegrade continence enema catheter in an appendiceal or cecal conduit, and to describe medium-term clinical outcomes. DESIGN: This study was a retrospective case series. SETTING: The study was conducted at a tertiary referral hospital in Sydney, Australia. PATIENTS: Adults administering antegrade colonic enemas to manage defecatory disorders were selected for the study. METHODS: Patients with an indwelling antegrade continence enema catheter completed a face-to-face survey when they attended the clinic for catheter change. A postal survey was sent to nonattenders, and, if it was not returned, the patient was contacted, and the survey was completed by telephone. The survey asked about irrigation techniques, satisfaction, confidence to manage, and continence, using quantitative scores. RESULTS: Fifty-four patients (45 female; mean age, 49 years) had constipation (n = 31), incontinence (n = 6), both incontinence and constipation (n = 2) or obstructed defecation due to gracilis neosphincter (n = 5), congenital anomalies (n = 8), or spinal injuries (n = 2). Thirty-five patients (65%) continued to irrigate for a mean follow-up of 5.5 years (range, 4 months to 13.7 years). Mean enema volume was 1178 mL (95% CI, 998–1357; range, 350–2000 mL), and half the patients added a stimulant to the irrigation. Mean total toileting time was 59 minutes (95% CI, 48–66; range, 15–120 minutes). Twenty-one patients had incontinence between irrigations, and in 17% incontinence was severe (St. Mark score >12). Satisfaction (visual analogue scale = 8.1) and confidence to partake in social activities (visual analogue scale = 8.2) and all-day activities (visual analogue scale = 7.1) were high. Complications included superficial wound infection (n = 15), wound infection requiring surgery (n = 6), paraconduit hernia (n = 2), and indwelling antegrade continence enema catheter dislodgement (n = 33). There was no conduit track stenosis. LIMITATIONS: The study is a medium-term retrospective case series using patient-reported outcomes and clinical records without a control group. CONCLUSIONS: With the use of the indwelling antegrade continence enema catheter, appendicostomy and cecostomy stenosis requiring revisional surgery was avoided. Antegrade colonic irrigation failed in about one-third of cases; in the 65% who continued to irrigate, satisfactory functional outcome was achieved.